Relative Age Effect and Biological Maturation on Inhibitory Control of Motor Response in Basketball - González G; Madinabeitia I.; Ureña N.; Alarcón F. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In the context of sports, relative age effect (RAE) generates transitional differences on maturational development non-linear at chronological age. This leads to a lack of selection opportunities in sport teams during pubertal stage. Biological maturation (BM) is the main modulator of these drastic changes in maturation, which affect sport performance. 34 young male basketball players [Mage= 10,94 (±1,51) years] are evaluated on inhibitory control of motor response through the computerized Go/no-go task. The study uses two BM indices: “maturity offset” and “percentage of adult height”. Results found significant differences on cognitive performance between two different chronological age groups (under10 / top10 years old.). Top10 players show a lower response time (RT) and accuracy adjusted response time than under10. However, the study does not find RAE (birth semester) on cognition. Percentage of adult height predicts both RT and accuracy adjusted RT performance in the entire sample, while maturity offset also did it, but only in the greater chronological age group (top10). Sports field research should consider BM control to explain RAE, and the influence on executive functions, that are crucial for interactive sport performance.